Impact of Mergers and Acquisitions announcement on shareholder value: An empirical evidence of short-term performance from Singapore market. - Nguyen, Thi Quynh Van (2013)
This thesis examines the impact of Mergers and Acquisitions announcements on shareholders wealth of acquirers in Singapore. In detail, this thesis will study the stock performance in response to M&A announcement under three time intervals: pre-announcement period (from day 5 to day 2 prior to announcement day), announcement period (including 1 day prior to announcement day and announcement day) and post-announcement period (from day 1 to day 5 after the announcement). The methodology to investigate this problem of interest is event study. The sample used in this study includes 165 M&A transactions taken place from 2000 to 2007 in Singapore market. Proxy of the market returns for the sample is Singapore Stock Exchange All Share (SGP). The result shows that M&A announcement will affect the shareholder value of acquirers. It is evidenced that during the announcement period from one day before until the day M&A announcements are actually made, shareholders of acquirers will receive significant positive abnormal returns. In addition, this thesis also examines different determinants, which may affect the abnormal returns of acquirers to identify their relationships. They are cross-border/domestic M&As, methods of payment and directions of mergers. Results show that those determinants do have positive impacts on stock performance of acquirers in particular periods.